PENGUKURAN KEPUASAN PELANGGAN HOTEL XYZ MENGGUNAKAN METODE SERVQUAL DAN IMPORTANCE PERFORMANCE ANALYSIS (IPA) - PURNANINGSIH, PUTRI RAGIL (Jurnal TIN Universitas Tanjungpura, 2017)
Hotel XYZ explain that reporting customer complaints related to facilities such as facilities and services that are less good. Based on observations of a complaint with every departemen then, to the holding of the study to measure how much the level of interest and satisfaction level of service to customer satisfaction at the Hotel XYZ. The purpose of this research is knowing the level of satisfaction and a customer, determine what attribute the service that needs to be prioritized, the analysis of gaps (gap) between the level of satisfaction and a customer, and made a proposal to improve the quality of service at the Hotel XYZ.The SERVQUAL, which is used in this study to measure the gap between consumer perceptions of service and the expectation, while the Importance-Performance Analysis (IPA) be used to analyze the appropriateness of and the performance of services, as well as the proposed improvements to do.Based on the results of research has been done by the average satisfaction level of the Hotel Merpati Pontianak to 20 atributes the quality of service is 3.860. But there are some attributes that must be improved as about the condition of the building when he’s doing the spread of the questionnaire and other attributes that has a value of the level of satisfaction is low and a high number of attributes that indicated on the service employees to visitors.proposed improvments that can be done to improve the quality of the attributes of the building condition by performing the checks, maintenance and improvement of the condition of the room and hotel facilities on a regular basis and can make a regular schedule or route area that should be prioritized for checking, maintenance and repair. To determine the conditions that need to be repaired, it can be done by specialized employees who are able to perform such work. Whereas the proposed improvement in employee services namely, with the addition of employees there are parts that need immediate attention but existing employees can not cope. A system of reward, punishment, training and briefing also can be done to improve the performance and morale of employees in order to know and understand the responsibilities of work, know the condition of the working environment, to improve the performance and knowledge customer service.Keyword ; The quality of service, SERVQUAL, Importance-Performance Analysis